Specifics of the Methodology of Comparative Analysis of the Ideational-Theoretical Foundations of Sinicized Marxism - Вілков, Вячеслав Юрійович; Назарков, Василь Костянтинович (Київський національний університет імені Тараса Шевченка, 2024)
The paper provides theoretical-methodological recommendations for improving the adequacy and heuristics of research on the origins of Chinese Marxist philosophical and socio-political thought in the 1940s–early 2020s, elucidating the attributive features and main tendencies in its rejuvenation. These recommendations are based on the analysis of methodological approaches to the theoretical reconstruction of the development of Marxist metanarratives in the USSR and the PRC. The author of the article proposes a scientific and theoretical justification for the analytical approach, according to which a specifically historically-oriented comparative method of studying Chinese Marxism should play a system-forming role. The model of cognition methodology structured according to this principle helped to reveal and give general characteristics to the defining ideological and institutional factors of the successive Sinicization of Marxism as the process and result of its transformation into such a nationally adapted variety of Marxist teaching, which became a philosophical foundation of the modern ideology, doctrine, and policy of the Communist Party of China, as well as the theoretical basis of the project and the state strategy of building “socialism with Chinese characteristics.” The paper’s material can contribute to improving the efficacy of further research into the logic of evolution and the specifics of interpretations of the axiomatics of the Marxist-Leninist paradigm in modern China; optimize the ideational-theoretical platform; and expand the methodological and conceptual tools for de-ideologized understanding and assessment of the direction of processes and possible prospects for the rejuvenation of Marxist teaching (Sinicized Marxism).

За результатами проведеного аналізу поширених у вітчизняній та зарубіжній літературі методологічних підходів до теоретичної реконструкції процесів розвитку марксистських метанарацій у СРСР та КНР в статті запропоновано теоретико-методологічні рекомендації щодо підвищення адекватності та евристичності досліджень генезису китайської марксистської філософської й суспільно-політичної думки 1940-х — початку 2020-х років, з’ясування її атрибутивних ознак і головних тенденцій оновлення. Автором статті запропоновано науково-теоретичне обґрунтування аналітичного підходу, відповідно до якого конкретно-історично орієнтований компаративний метод вивчення китайського марксизму має виконувати роль системотвірного. Структурована за таким принципом модель методології пізнання допомогла виявити й узагальнено охарактеризувати визначальні ідейні та інституційні чинники послідовної китаїзації марксизму як процесу й результату перетворення його на такий національно-особливий різновид марксистського вчення, який став філософським фундаментом сучасної ідеології, доктрини й політики Компартії Китаю, теоретичною основою проєкту та державної стратегії побудови «соціалізму з китайською специфікою».Використання статейного матеріалу може сприяти підвищенню ефективності подальших досліджень логіки еволюції й специфіки інтерпретацій аксіоматики марксистсько-ленінської парадигми в сучасному Китаї; оптимізувати ідейно-теоретичну платформу й розширити методологічний і понятійний інструментарій для деідеологізованого розуміння й оцінки спрямованості процесів і ймовірних перспектив модернізації марксистського вчення (китаїзованого марксизму) в КНР.
Особливості методології компаративного аналізу ідейно-теоретичних засад китаїзованого марксизму
Keywords: Marxism-Leninism; Soviet Marxism; Chinese Marxism; Adaptation of Marxism to the Chinese context; Sinicized Marxism; Socialism with Chinese Characteristics; марксизм-ленінізм; радянській марксизм; китайський марксизм; китаїзація марксизму; китаїзований марксизм; соціалізм із китайською специфікою